Pengembangan Reconfigurable Low Power Monitoring System dan Pengendali Kualitas Udara menggunakan Finite State Machine berbasis ESP8266 - Fikri Miftah Akmaludin; Agung Setia Budi; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Boarding rooms as a place to live should have good air quality. The most common causes of decreased indoor air quality are poor air circulation and contamination from harmful gases, one of which is carbon monoxide (CO) which is commonly found in cigarette smoke and vehicle emissions. Tool developed in this research is expected to reduce the potential dangers that may arise from high concentration of carbon monoxide gas and discomfort due to hot and humid room air. The system is designed to detect ambient air quality using the DHT22 and MQ7 sensors, and uses a fan and exhaust to control air quality. The system is built with a parameter threshold that can be reconfigured. This system is also made using a finite-state machine algorithm to define several states that represent each existing process. One of them is a deep sleep state for power saving, this is needed because the system will operate continuously, the method used is taking advantage of the deep sleep mode on the low power feature of ESP8266 chip. From the test results, it's known that this tool successfully performs its function, and is able to reduce current consumption by 34.82 mA under ideal conditions.